IMPLEMENTASI PROGRAM PENGEMBANGAN DESTINASI WISATA ALAM LABUAN CERMIN OLEH DINAS KEBUDAYAAN DAN PARIWISATA KABUPATEN BERAU - Agus Neksen Neri (Journal of Policy & Bureaucracy Management, 2020)
Tourism is one of the mainstays of Berau Regency to be developed. Therefore, the Berau District Government has established a number of policies, including increasing the promotion of natural and cultural tourism objects. This study aims to describe and analyse the implementation of the Labuan Cermin tourist destination development program in the Subdistrict of Biduk-biduk by the Berau Regency Culture and Tourism Office. The result of the study shows that the implementation of the Labuan Cermin tourist destination development program in the Subdistrict of Biduk-biduk by the Berau Regency Culture and Tourism Office has done quite well. However, there are several obstacles such as limited budget and area status, limited accessibility to tourist objects, tour and travel agents that have not been well coordinated, lack of public understanding of partnership. The community is quite active in infrastructure development, but there are still some people who are still less concerned with the development that is taking place in their village.